Microabrasion as treatment of enamel fluorosis - Ana Caroline Brito; Renato da Costa Ribeiro; Raimundo Rosendo Prado Júnior; Teresinha Soares Pereira Lopes (Faculdade São Leopoldo Mandic, 2008)
There is currently a trend in favor of using fluoride as a coadjuvant in reducing caries indexes, as much in underdeveloped as in developedcountries. However, simultaneously the indexes of dental fluorosis seem to grow in an inverse proportion. This is brought about by chronic ingestion of fluoride for a prolonged length of time or in high concentration. Enamel microabrasion is an effective method to remove superficial stains caused by this condition, which affects esthetics of that tissue. The use of 18% hydrochloric acid in association with pumice, despite being a simple and low cost method, has been gradually replaced due to its potential of causing damage to periodontal tissues. Thus, this article reports the treatment of a fluorosis clinical case solved with microabrasion using phosphoric acid 37%, because its costbenefit is supposedly better than with chloridric acid. The deliberate ingestion of toothpaste was the probable cause of the tooth stains. Due to the location of the teeth and to the patient's smile, only the six upper anterior teeth were selected to receive the proposed treatment. Four clinical sessions, with a seven days interval between each other, were carried out using 37% phosphoric acid and pumice. Under rubber dam isolation, the two first sessions consisted of rubbing the acid-pumice mix on enamel surface using a rubber cup on slow speed, and abrasive paper strips on the interproximal tooth surfaces. On the two final sessions, only finishing touches were performed using a wooden spatula to manually rub the acid-pumice paste.